Modified absolute value cumulating spectrum sensing algorithm in cognitive radio - Zhiyong HE (Dianxin kexue)
Absolute value cumulating (AVC) algorithm is a common spectrum sensing method in Laplacian noise (LED) surroundings,however,the ‘spikes or outliers' in Laplacian noise can't be fully smoothed,which results in bad detection performance.Aiming at this problem,an modified AVC spectrum sensing algorithm was proposed.The principle was to do the processing of the absolute value of the received signal and the processing result was accumulated as the test statistic to determine whether there was the main user and realize the spectrum sensing.In addition,the central limit theorem was used to deduce the probability density curve of the proposed test statistic in the absence of the primary user,and the theoretical decision threshold was given.Numerical results show that the proposed algorithm outperforms the AVC sensing algorithm and energy detection algorithm with Laplacian noise about 1 dB and 4 dB respectively.